Youth entrepreneurship in the Republic of Kazakhstan: concept, problems and solutions - Aitzhanova, D.N; Begentayev М.М.; Kunyazova S.К.; Titkov А.А. (BUKETOV BUSINESS REVIEW, 2021)
Object: The inclusion of the younger generation in entrepreneurial activities is one of the solutions to the problem of employment, especially aggravated during the COVID-19 pandemic. Considering the importance of the development of youth entrepreneurship for the processes of innovative transformation of the economy, as well as the relevance of managing the process of social adaptation of young people, involving them in creative activities and providing opportunities for maximum personal self realization, it can be argued that the mechanism for supporting and developing youth entrepreneurship is a central element in solving social and economic development of the Republic of Kazakhstan. The purpose of this study is to analyze the causes of youth unemployment in order to determine the variable forms and types of youth entrepreneurship aimed at solving the problems of youth employment. Methods: The collected theoretical and practical data on the cause-and-effect factors of the functioning of youth entrepreneurship were analyzed using the methods of system analysis, structuring information, building hypotheses and polling. Findings: On the basis of scientific approaches to understanding the structural elements of youth, the conceptual essence of youth was systematized, an objective approach to the concept of youth entrepreneurship was determined, which was considered in accordance with its target, aimed at carrying out entrepreneurial activities. Moreover, the cause-and-effect factors of the development of youth entrepreneurship have been determined, a classification of youth entrepreneurship has been developed according to the main types. Through a survey the situation on the labor market regarding the problems of the development of youth entrepreneurship was studied and ways of solving the problem of youth unemployment were proposed. Conclusions: A clear systematization of scientific approaches to the concept of youth entrepreneurship, identification of the causes of youth unemployment, problems of the development of youth entrepreneurship will ensure the progressive development of youth entrepreneurship to achieve full employment of youth and the population in the labor market.